A right result? : Advocacy, justice and empowerment - Henderson, Rick (Book collections on Project MUSE., 2001)
As the prospect of a legal right to advocacy inches closer, so the need to scrutinise its key values and practices becomes urgent. Although widely acclaimed as a 'good thing', there is little agreement as to how advocacy should be implemented, funded or evaluated. This book offers the first comprehensive analysis of the benefits of advocacy.